Protective effects of dioscin against cisplatin‐induced nephrotoxicity via the microRNA‐34a/sirtuin 1 signalling pathway. (5th July 2017) - Zhang, Yimeng; Tao, Xufeng; Yin, Lianhong; Xu, Lina; Xu, Youwei; Qi, Yan; Han, Xu; Song, Shasha; Zhao, Yanyan; Lin, Yuan; Liu, Kexin; Peng, Jinyong
Abstract : Background and Purpose: Dioscin exhibits a range of pharmacological actions but little is known of its effects on cisplatin (CDDP)‐induced nephrotoxicity. Here, we have assessed the effects and the possible mechanisms of dioscin against CDDP‐induced nephrotoxicity. Experimental Approach: We used an in vivo model of CDDP‐induced nephrotoxicity in rats and mice and, in vitro, cultures of NRK‐52E and HK‐2 cells. The dual luciferase reporter assay was used to demonstrate modulation, by dioscin, of the targeting of sirtuin 1 (Sirt1) by microRNA (miR)‐34a. Molecular docking assays were used to analyse the effects of dioscin with Sirt1, Keap1 and NF‐κB. Key Results: Dioscin attenuated cell damage in vitro and decreased renal injury in rats and mice, treated with CDDP. In terms of mechanisms, dioscin reversed CDDP‐induced up‐regulation of miR‐34a and thus up‐regulated Sirt1 levels. In addition, dioscin altered levels of haem oxygenase 1, glutathione‐cysteine ligase subunits (GCLC, GCLM) and Keap1, along with increased nuclear translocation of Nrf2, thus decreasing oxidative stress. Also, dioscin affected levels of AP‐1, COX‐2, HMGB1, IκB‐α, IL‐1β, IL‐6 and TNF‐α and decreased the ratio of acetylated NF‐κB and normal NF‐κB, to suppress inflammation. From molecular docking assays, dioscin directly bound to Sirt1, Keap1 and NF‐κBp65 by hydrogen bonding and/or hydrophobic interactions. Conclusions and Implications: Our results have linked CDDP‐induced nephrotoxicity and the miR‐34a/Sirt1 signalling pathway, which was modulated by dioscin. This natural product could be developed as a new candidate to alleviate CDDP‐induced renal injury.